The Process of Handling Ship Arrivals in the Inapornet System at PT. Gemalindo Sukses Bahari Dumai - Rico Rivaldi Siregar; Eka Fransiska (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
The purpose of this study is to find out how the process of ship arrival at PT. Gemlindo Sukses Bahari in the inapornet system in order to be able to carry out unloading/loading activities at Dumai port. In conclusion, in the activity of handling the arrival of the ship of PT. Gemalindo Sukses Bahari is required to carry out appropriate and efficient activities so that the ship service agency process can run smoothly. All activities have been organized to reduce errors when carrying out ship arrival handling activities. PT. Gemalindo Sukses Bahari is a company engaged in ship agency services. The process of ship agency services at PT. Gemalindo Sukses Bahari starts from the beginning of the arrival of the ship, unloading activities until the ship departs to the next destination port. Ship agency service procedures at PT. Gemalindo Sukses Bahari includes the arrival and departure of ships. The ship service agency system starts from the arrival of the ship, then makes permits that are submitted to Syahbandar, Pelindo and the Port Health Quarantine Office, seat applications to Syahbandar and Pelindo, the last ship service is the making of exit permits submitted to Syahbandar, for ship departure services, ship agencies in the form of managing ship documents while docked at the port. In this paper research, the author uses field research and library research. The results of the research on the process of handling ship arrivals in the Inaportnet system often have obstacles, namely, delays in ships entering or leaving the port due to delays in documents prepared by ship agents, therefore in docking ships, must be handled by professional workers.